Impact of human activities on the concentration of indoor air particles in an antarctic research station - Pagel, Erica Coelho (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2017)
One of the main characteristics of Antarctic buildings is the fact that they are designed mostly with a focus on energy efficiency. Although human activity is a major source of pollution, indoor air quality is not a matter of significant concern during building planning. This study examines the relationship between indoor activities in an Antarctic Research Station and the size distribution of particulate matter. Real-time particle size distribution data is used in conjunction with time-activity data. The activity number ratio is calculated using the mean number of particles found in each size range during each activity divided by the average number of particles found during a period characterized by the absence of human activities. Cooking, the use of cosmetics, waste incineration and exhaust from light vehicles were responsible for significant deterioration of indoor air related to the presence of fine and ultrafine particles. Cleaning, physical exercise and the movement of people were responsible for the emission of coarse particles. This article emphasizes the importance of post-occupancy evaluation of buildings, generating results relevant to the planning and layout of new buildings, especially regarding better indoor air quality.